Stable Fly Stomoxys calcitrans (L.) (Insecta: Diptera: Muscidae): EENY642/IN1114, 10/2022 - Kaufman, Phillip E.; Burgess IV, Edwin R.; Weeks, Emma N. I. (EDIS, 2022)
Updated by Edwin R. Burgess IV. Originally written by Phillip E. Kaufman and Emma N. I. Weeks, January 2016.